CELIAC DISEASE: FROM PATHOGENESIS TO TREATMENT - S. V. Bel'mer; T. V. Gasilina (Вопросы современной педиатрии, 2013)
Celiac disease is characterized by intolerance to gluten, which is a protein composite of grain species. The prevalence of this condition in Europe and USA is 1:100–1:500. Gluten can indirectly initiate immune response through the molecules of major histocompatibility complex I and II. Changes in gluten tolerance are likely to be a key factor of celiac disease development, with increase of epithelial barrier permeability having the primary role in gluten intrusion into the mucous membrane and immune response initiation. Treatment of celiac disease at present is based on strict lifelong gluten free diet with exception of grain species containing gluten (wheat, rye, barley) and certain products of their processing. Safe threshold of gluten contain in food is considered to be 20 ppm (parts per million). The optimal management decision is intake of manufactured gluten free products, which are totally safe, variously represented and have good organoleptic characteristics. Appropriate diet in combination with correction of secondary metabolic disturbances and treatment of associated disorders can provide high life quality in patients with celiac disease.